2013
DOI: 10.1002/ajh.23452
|View full text |Cite
|
Sign up to set email alerts
|

Molecular monitoring and stepwise preemptive therapy for Epstein–Barr virus viremia after allogeneic stem cell transplantation

Abstract: The optimal preemptive therapy for Epstein-Barr virus (EBV)-associated diseases remains under discussion. We developed a stepwise preemptive therapy (antiviral agents and reduction of immunosuppressants [RI] followed by rituximab) for EBV viremia, based on duration of EBV viremia and changes of viral loads. The blood EBV-DNA loads were regularly monitored by quantitative real-time polymerase chain reaction in 251 recipients undergoing allogeneic stem cell transplantation. The 3-year cumulative incidence of EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 37 publications
0
48
2
Order By: Relevance
“…No CMV disease or EBVrelated post transplantation lymphoproliferative disorder developed in this study may also due to preemptively treating for viremia. 44,45 Similar to ISD-HSCT, the NRM in our haplo-cord-HSCT was lowered than others after UCBT or HID-HSCT alone. 31,46 The haplograft would achieve reliable early engraftment, which may contribute to the low incidence of post transplant neutropeniarelated infections and the low rate of NRM.…”
Section: Discussionmentioning
confidence: 65%
“…No CMV disease or EBVrelated post transplantation lymphoproliferative disorder developed in this study may also due to preemptively treating for viremia. 44,45 Similar to ISD-HSCT, the NRM in our haplo-cord-HSCT was lowered than others after UCBT or HID-HSCT alone. 31,46 The haplograft would achieve reliable early engraftment, which may contribute to the low incidence of post transplant neutropeniarelated infections and the low rate of NRM.…”
Section: Discussionmentioning
confidence: 65%
“…Ganciclovir was given for 2 weeks pre-transplantation for prophylaxis of CMV infection, and was administered once again when CMV-emia occurred [4]. Preemptive therapy for EBV-emia was according to our previous description [38, 41]. Antifungal agents were administered 5 days pre-transplantation and continued for +30 to +90 days post-transplantation or disease control according to the history and state of IFD pre-transplantation [42].…”
Section: Methodsmentioning
confidence: 99%
“…11 RIT is often used as prophylaxis for PTLD, particularly in pediatric patients at high risk for PTLD development, including those with severe aplastic anemia after unrelated cord blood transplantation, or after haploidentical HSCT. 12,13 However, RIT use after allogeneic HSCT can deplete both donor and recipient B cells, causes a delay in B-cell immune reconstitution of at least 6 months, 14 and therefore can result in increased incidences of critical cytopenia and infections. 15,16 In the current study, we found that RIT use before HSCT reduced of methylprednisolone, and tacrolimus for the prevention of graft rejection.…”
Section: Discussionmentioning
confidence: 99%